Coal exploitation and income inequality: Testing the resource curse with econometric analyses of household survey data from northwestern China. (30th November 2021) - Wen, Qi; Li, Jin; Mwenda, Kevin M.; Ervin, Daniel; Chatterjee, Maya; Lopez‐Carr, David
Abstract: Coal resources have always been an important driving force for macroeconomic growth and GDP growth in resource‐rich regions. However, this growth has also caused inequality of household income in developing regions. Using survey data on rural household livelihoods in Shenmu county, Shaanxi Province, in northwestern China, this paper analyzes the relationship between coal exploitation and income inequality. Four multivariate econometric analyses are developed. We find evidence for the resource curse theory of natural resource exploitation leading to inequality: the Gini coefficient for household revenue is discovered to be markedly related with the location of and participation in coal exploitation. Nevertheless, this correlation is not linear. Rather, household income inequality primitively rises with environmental and resource subsidies. We analyze the impacts of household income inequality and contrast the characteristics of household livelihood and location characteristics in the coal exploitation site of northern Shenmu with those in the whole survey site. Our statistical analysis shows that out‐migration, the level of total household income, and convenience of household transportation are the important elements devoting to household income in northern Shenmu, the coal resources endowment region. However, the environmental damage and pollution caused by coal exploitation has substantial negative impacts upon household income, especially for households not participating in coal activities. Overall, we found that coal exploitation did not develop local industries. Adversely, the ecological environment problem and the high subsidy for coal mining caused by the exploitation of coal resources have aggravated the inequality of household income in the sample areas. Additionally, the development of coal resources attracted youth labor from agriculture to the coal industry, which exacerbated the lack of labor force and weakened village agricultural productivity.